Coprecipitation synthesis and microstructure characterization of nanocomposite SrCr2O4/MXene. (15th March 2022) - Akhtar, Naseem; Rani, Malika; Mahmood, Arshad; Khan, Shamim; Murtaza, G.; Arbab, Sobia; Batool, Kiran; ALOthman, Zeid A.; Ouladsmane, Mohamed; Ali, Sajid; shah, Aqeel
Abstract: In this work, we synthesize the strontium chromite SrCr2 O4 using sol gel method. Then by using coprecipitation method nanocomposite SrCr2 O4 /MXene (Ti3 C2 ) was synthesized for achieving better ionic storage. Structural and surface morphology of nanocomposite is investigated using XRD, and SEM. Further characterizations are performed using Raman Spectroscopy, photoluminescence and EDX. The band gap, as measured from UV–Vis spectrum, is reduced to 2.20 eV for nanocomposite SrCr2 O4 /MXene (Ti3 C2 ) from a value of 3.51 eV for SrCr2 O4 . The obtained results agree with previous literature. The average crystalline size for nanocomposite SrCr2 O4 /MXene (Ti3 C2 ) is 25.1 nm. All crystal peaks match with Fm-3m (225) space group having cubic spinel crystal structure. Elemental composition of the prepared samples was confirmed by EDX spectrum. The prepared nanocomposite is proposed as a potential material for higher electrocatalytic activity.